Determinants of transaction costs in construction projects - Li, Huimin; Arditi, David; Wang, Zhuofu (Journal of Civil Engineering and Management, 2015)
Transaction costs occur when a good or service is transferred across a technologically separable interface, and include the costs of drafting, negotiating and enforcing an agreement, and also the costs of governance and bonding to secure commitments. In the complex and high risk environment of a construction project, questionable decisions can be made in the planning and design phase, and disagreements, conflicts, disputes, change orders, and claims can occur in the construction phase. These problems contribute to an increase in transaction costs. Transaction costs at the pre-contract phase of a project are different from the transaction costs at the post-contract phase. However, there is no consensus on a standard definition of transaction costs in construction projects. In this study, a detailed literature review focusing on transaction costs in construction project management is presented. The factors that affect transaction costs are identified and categorized under the headings of the owner’s and contractor’s roles in the transaction, project management efficiency, and the characteristics of the transaction environment.